ChemInform Abstract: From Liquid to Solid‐State Fluorescence: Tricyclic Lactones Based on 4‐Hydroxy‐1, 3‐thiazoles. Issue 25 (24th June 2014) - Calderon Ortiz, Lorena K.; Wuerfel, Hendryk; Taeuscher, Eric; Weiss, Dieter; Birckner, Eckhard; Goerls, Helmar; Beckert, Rainer
Abstract The compounds′ fluorescence properties in solid state as well as in polar solvents (EtOH, DMSO) in absence and presence of NaOH and HCl are examined.